Assessment of Restored Kidney Transplantation Including the Use of Wider Criteria for Accepting Renal Donors After Cancer Excision. Issue 11 (November 2019) - Sprott, Philip; Hibberd, Adrian D.; Heer, Munish K.; Trevillian, Paul R.; Clark, David A.; Johnson, David W.; Oldmeadow, Christopher; Chiu, Simon; Attia, John R.
Abstract : Background: The transplantation of kidneys after cancer excision (restored kidney transplantation, RKT) warrants further evaluation as a source of kidneys for transplantation. We determined whether larger cancers can be safely transplanted, the risks of adverse events from RKT, and whether RKT confers a survival advantage for patients waiting for transplantation. Methods: In a retrospective cohort study, 23 dialysis patients awaiting transplant underwent RKT at John Hunter Hospital, Australia between 2008 and 2015. Patients were >60 years old and accepted onto the National Organ Matching Service. This RKT Group was divided into donor renal cancers ⩽30 mm and >30–⩽50 mm. Adverse event profiles for RKT recipients were compared with 22 standard live donor recipients using logistic regression analyses. Recipient and transplant survivals for RKT were compared with 2050 controls from Australian New Zealand Dialysis Transplant Registry using Cox regression models. To increase statistical power for survival analyses, data from 25 RKT recipients from Princess Alexandra Hospital, Brisbane were added, thus creating 48 RKT recipients. Results: There were no significant differences in mortality, transplant failure nor AEs between the 2 cancer Groups. RKT increased the risks of Adverse event profiles (odds ratio: 6.48 [2.92–15.44]; P < 0.001). RKT reduced mortality risk by 30% (hazard ratio [HR]: 0.70 [0.36–1.07]; P = 0.299) compared with those continuing on the transplant list who may or may not be transplanted. RKT significantly reduced mortality risk for those remaining on dialysis (HR: 2.86 [1.43–5.72]; P = 0.003). Transplant survival for RKT was reduced compared with control deceased donor (HR: 0.42 [0.21–0.83]; P = 0.013) and live donor transplants (HR: 0.33 [0.02–0.86]; P =0.023). Conclusions: The use of larger carefully selected cancer-resected kidneys for transplantation appears safe and effective. RKT confers a possible survival advantage compared with waiting for transplantation, an increased survival compared with those remaining on dialysis but reduced transplant survival.